Reframing the New Mestiza: Identity Politics and Social Commitment in Chicana Art - Lobo, Patricia A. (Hungarian Journal of English and American Studies, 2021)
This article offers an interdisciplinary approach to some of the most iconic pieces of Chicana Art using Gloria Anzaldúa’s Borderlands/La Frontera. Parallels between the textual and visual representations of identity politics and social commitment in Chicana feminist art and Anzaldúa’s work, respectively, will be established through the concepts of “Borderlands” and “New Mestiza” as interpretation keys. The article begins by addressing representations of geographical borders as a unifying theme; then, it establishes a correlation between the concepts “Borderlands” and “New Mestiza,” and the reformulation of female identity represented in Chicana visual art. Finally, it will explore the purpose of the social commitment of the author/artists and how it is represented in their literary/artistic productions. The visual art of the selected Chicana visual artists, including Ester Hernández, Yolanda M. López, Alma López, Santa Barraza, and Judith Baca, accurately portray the experience of Chicana women theorized in Borderlands/La Frontera. (PAL)